PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI BENTUK ALJABAR KELAS VII MTS YPKS PADANGSIDIMPUAN - Akid Nasution, Muhammad; Panjaitan, Agus Makmur; Nilasari Harahap, Adek (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
The research aims to determine the effect of implementing the cooperatif learning model type Think Pair  and Share.This type of research is Quasi Research Experiments. The subjects of the study were classes VII-1 and VII-2 of 40 people. Women as many as 20 men and 20 men.The object taken in this study is the use of TPS learning models in an  effect of implementing of student learning concepts on algebraic subjects.the test results against the math problem solving level students obtained an average score of experimental group = 78.35 with the criteria "medium-skilled" and the control group = 72.5 with the criteria "medium-skilled". The test normality of the experiment class pretes obtained L0 = 0.1793< 0.190= Ltabel, while the control class pretes normality test obtained L0 = 0.1806 < 0.190= Ltabel. The experiment and control grade pretes homogeneity test was obtained at pretes Fhitung = 1,338 < 2.15 = Ftabel . Test normality postes class experiment obtained L0 = 0.1761< 0.190= Ltabel while and Test normality postes class control obtained L0 = 0.1352 < 0.190= Ltabel. Test homogeneity postes class experiments and controls obtained on on postes obtained Fhitung = 1,193 < 2.15 = Ftabel . For hypothesis test obtained thitung = 8.13 > 2.024= ttabel With dk numerator 2 and dk denominator 38 and odds of 0.95 (α = 0.05). Then H0 was rejected and Ha accepted.